Method for detecting element content of solid electrolyte material

Through high-temperature pyrolysis and sodium hydroxide solution, and combined with ICP-OES and IC testing, the problem of cumbersome and low accuracy of the detection of inorganic element content in LiAlPO4F materials is solved, and the accurate amount of element content of LiAlPO4F electrolyte material is achieved. The determination simplifies digestion processing and improves the scientificity and accuracy of the detection.

CN119310069APending Publication Date: 2025-01-14LIONGO (CHANGZHOU) NEW ENERGY CO LTD

Patent Information

Application Number
CN202411457715.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing inorganic element content detection methods in inorganic solid electrolyte materials have problems such as cumbersome operation and low accuracy. Especially in LiAlPO4F materials, the combination of fluorine and aluminum elements affects the digestion process and subsequent analysis, and lacks effective testing standards.

Method used

The LiAlPO4F solid electrolyte sample is directly pyrolyzed at high temperature, and the F element generated by decomposition is collected through sodium hydroxide solution, combined with inductively coupled plasma emission spectroscopy and ion chromatography to test the content of lithium, aluminum and phosphorus elements to avoid the digestion of acid solutions. High aluminum and high fluorine coexist to form aluminum fluoride substances that are not easily soluble in water, simplifying digestion treatment.

Benefits of technology

The accurate measurement of the element content of LiAlPO4F electrolyte material is achieved, with simple operation and high scientific detection methods, avoiding the generation of aluminum fluoride substances that are not easily soluble in water, and improving the accuracy and simplicity of detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092624190000141
    Figure BDA0005092624190000141
  • Figure BDA0005092624190000151
    Figure BDA0005092624190000151
Patent Text Reader

Abstract

The invention provides a solid electrolyte material element content detection method, which comprises: a) carrying out heating treatment on a to-be-detected LiAlPO4F electrolyte material in the presence of a shielding gas to obtain a contact material; introducing the protective gas tail gas into alkali liquor to obtain a first contact material solution; b) digesting the contact material obtained in the step a) in the presence of acid to obtain a second contact material solution; and c) testing the contents of lithium, aluminum and phosphorus elements in the second contact material solution by inductively coupled plasma atomic emission spectrometry, and testing the contents of fluorine elements in the first contact material solution and the second contact material solution by ion chromatography, thereby completing the detection of the element contents of the LiAlPO4F electrolyte material. Compared with the prior art, the detection method provided by the invention has the advantages that specific steps are adopted, overall better interaction is realized, the content of each element in the LiAlPO4F electrolyte material can be accurately and effectively quantitatively determined, the operation is simple, and the detection method is more scientific.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of detection methods, and more specifically, to a method for detecting the element content of a solid electrolyte material. Background Art

[0002] Since its commercialization in 1991, lithium-ion batteries have been widely used in various industries due to their excellent performance. At present, electrolytes composed of organic solvents and lithium salts are the main electrolytes for lithium-ion batteries, but they are flammable, leaky, and easy to dendrite. The safety issues brought about by them hinder the further application of lithium-ion batteries. Inorganic solid electrolytes have many advantages such as superior chemical, mechanical and thermal stability, and are increasingly attracting people's attention.

[0003] At present, the main methods for determining the content of inorganic elements in inorganic solid electrolytes include chemical analysis, atomic absorption, X-ray fluorescence spectroscopy, and inductively coupled plasma emission spectrometry. Among them, chemical analysis and spectral analysis are suitable for analyzing metal elements in liquid samples, but are not suitable for the analysis of most non-metallic elements; and it is often necessary to first digest the inorganic solid electrolyte sample in an acidic and high temperature environment, because some elements combine with acid radical ions to form precipitation and cannot be completely digested; or the acid radical used in digestion has the same chemical composition as the inorganic solid electrolyte, so that the result analysis cannot be performed. For example, patent CN110931847B discloses a method for detecting the content of inorganic elements in lithium titanium aluminum phosphate solid electrolyte materials. This method requires first heating the solid electrolyte material with an alkaline substance at high temperature, then dissolving some elements with a solvent, and then replacing the solvent to dissolve the undissolved part again. The operation process is very cumbersome and has low accuracy. For example, patent CN109540874B discloses a method for detecting the content of inorganic elements in a sample of a lithium lanthanum zirconium oxygen type solid electrolyte. The sample is first melted, HF is added for digestion, and the residue is filtered and then alkali is added to dissolve it until it is completely dissolved. Acid and alkali solutions are used for treatment at the same time, and the operation is very complicated.

[0004] LiAlPO4F (LAPF: lithium aluminum fluoride phosphate) has become an ideal solid electrolyte for lithium-ion batteries due to its high total ion conductivity and excellent chemical and thermal stability. However, at present, there are no public literature reports or test standards for the test of the content of inorganic non-metallic elements in LiAlPO4F compounds, a new type of solid electrolyte material. In addition, LiAlPO4F materials contain both fluorine and aluminum elements. In the solution, fluorine and aluminum are easily combined to form aluminum fluoride substances that are insoluble in water and acid, thus affecting the digestion process and subsequent element content test analysis. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a method for detecting the element content of a solid electrolyte material, which comprises directly pyrolyzing a sample of a LiAlPO4F solid electrolyte at high temperature, collecting the F element generated by decomposition with a sodium hydroxide solution, performing ion chromatography analysis, obtaining the content of the fluorine element, further digesting the remaining solid, and finally testing the element content using ICP-OES (inductively coupled plasma emission spectrometer) and IC (ion chromatograph), and obtaining an accurate result through mathematical calculation; on this basis, the coexistence of high aluminum and high fluorine to generate aluminum fluoride substances that are not easily soluble in water when directly digesting with an acid solution is avoided; at the same time, the decomposition product obtained after high-temperature pyrolysis pretreatment only needs a simple digestion treatment to obtain a completely digested sample.

[0006] The present invention provides a method for detecting the element content of a solid electrolyte material, comprising the following steps:

[0007] a) heating the LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; passing the protective gas tail gas into an alkali solution to obtain a first contact material solution;

[0008] b) digesting the contact material obtained in step a) in the presence of an acid to obtain a second contact material solution;

[0009] c) The contents of lithium, aluminum and phosphorus in the second contact material solution are tested by inductively coupled plasma atomic emission spectrometry, and the contents of fluorine in the first contact material solution and the second contact material solution are tested by ion chromatography to complete the detection of the element content of the LiAlPO4F electrolyte material.

[0010] Preferably, the protective gas in step a) is continuously introduced; the speed of the continuous introduction is 5 mL / min to 20 mL / min.

[0011] Preferably, the heating rate of the heating treatment in step a) is 2°C / min to 8°C / min, the temperature is 700°C to 1000°C, and the holding time is 0.5h to 2h.

[0012] Preferably, the alkali solution in step a) is a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution; the concentration of the alkali solution is 0.1 mol / L to 1 mol / L.

[0013] Preferably, the acid in step b) is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid;

[0014] The dosage ratio of the acid to the contact material is (50-100) mL / g.

[0015] Preferably, the digestion heating rate in step b) is 2°C / min to 8°C / min, the temperature is 100°C to 220°C, and the insulation time is 30min to 360min.

[0016] Preferably, the process of the inductively coupled plasma atomic emission spectrometry test in step c) is specifically as follows:

[0017] (1) Pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside;

[0018] (2) The second contact material solution is diluted to 50 g with 3% nitric acid solution, 1 mL is weighed into a centrifuge tube, diluted to 50 mL with ultrapure water, shaken well, and set aside;

[0019] (3) Start the inductively coupled plasma emission spectrometer, set the test conditions, and after the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0020] Preferably, the test conditions in step (3) are:

[0021] The RF power is 1 kW to 1.5 kW, the stabilization time is 10 s to 20 s, and the observation mode is radial.

[0022] Preferably, the process of the ion chromatography test in step c) is specifically as follows:

[0023] (1) Accurately pipette 1 mL of the F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake it well; using this solution as the mother solution, prepare a standard curve with a concentration gradient of 0.01 ppm, 0.02 ppm, 0.05 ppm, 0.1 ppm, 0.2 ppm, 0.5 ppm, and 1 ppm, shake it well, and set aside;

[0024] (2) Accurately weigh 1 g of the sample into a centrifuge tube, dilute to 50 g with ultrapure water, shake well, and set aside;

[0025] (3) Start the ion chromatograph, set the test conditions, and after the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. The standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated according to the content;

[0026] The fluorine content in the sample to be tested is obtained by subtracting the fluorine content in the blank alkali solution as in step a) from the fluorine content in the first contact material solution and the second contact material solution measured by the above ion chromatography.

[0027] Preferably, the test conditions in step (3) are:

[0028] Eluent A: 5mmol / L~10mmol / L sodium carbonate aqueous solution;

[0029] Eluent B: 15mmol / L~25mmol / L sodium carbonate 30%~50% acetonitrile aqueous solution;

[0030] Eluent flow rate: 0.5mL / min~1mL / min;

[0031] Injection volume: 10μL~30μL;

[0032] Column oven temperature: 30℃~50℃.

[0033] The invention provides a method for detecting the element content of a solid electrolyte material, comprising the following steps: a) heating a LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; passing the tail gas of the protective gas into an alkali solution to obtain a first contact material solution; b) digesting the contact material obtained in the step a) in the presence of an acid to obtain a second contact material solution; c) testing the contents of lithium, aluminum and phosphorus in the second contact material solution by inductively coupled plasma atomic emission spectrometry, and testing the contents of fluorine in the first contact material solution and the second contact material solution by ion chromatography, thereby completing the detection of the element content of the LiAlPO4F electrolyte material. Compared with the prior art, the detection method provided by the present invention utilizes the property of LiAlPO4F material to decompose and release F at high temperature, reduces the F content in the material by heating treatment, and avoids the coexistence of high aluminum and high fluorine to generate aluminum fluoride substances that are not easily soluble in water when directly digested with an acid solution; the decomposition products obtained after high-temperature pyrolysis treatment only need simple digestion treatment to obtain a completely digested sample; ICP-OES and IC are then used to test the element content, and accurate results can be obtained through mathematical calculations; the above technical scheme achieves overall good interaction, can accurately and effectively quantitatively determine the content of each element in the LiAlPO4F electrolyte material, is simple to operate, and the detection method is more scientific. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention provides a method for detecting the element content of a solid electrolyte material, comprising the following steps:

[0036] a) heating the LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; passing the protective gas tail gas into an alkali solution to obtain a first contact material solution;

[0037] b) digesting the contact material obtained in step a) in the presence of an acid to obtain a second contact material solution;

[0038] c) The contents of lithium, aluminum and phosphorus in the second contact material solution are tested by inductively coupled plasma atomic emission spectrometry, and the contents of fluorine in the first contact material solution and the second contact material solution are tested by ion chromatography to complete the detection of the element content of the LiAlPO4F electrolyte material.

[0039] The present invention firstly heats the LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; and passes the tail gas of the protective gas into an alkali solution to obtain a first contact material solution.

[0040] The present invention has no special restrictions on the source of the LiAlPO4F electrolyte material to be tested, and commercially available solid electrolytes or self-made products known to those skilled in the art can be used. The present invention has no special restrictions on the type and source of the protective gas, as long as it can prevent danger during the heating process; in a preferred embodiment of the present invention, the protective gas is dry air.

[0041] In the present invention, the protective gas is preferably continuously introduced; the speed of continuous introduction is preferably 5 mL / min to 20 mL / min, more preferably 10 mL / min to 15 mL / min; the tail gas of the protective gas is introduced into the alkali solution to obtain the first contact material solution.

[0042] In the present invention, the heating rate of the heat treatment is preferably 2°C / min to 8°C / min, more preferably 5°C / min, the temperature is preferably 700°C to 1000°C, more preferably 700°C to 800°C, the holding time is preferably 0.5h to 2h, more preferably 1h; and the contact material is obtained by natural cooling.

[0043] In the present invention, the alkali solution is preferably a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution, more preferably a sodium hydroxide aqueous solution; wherein the water used is preferably deionized water and / or distilled water, and the present invention has no special restrictions on this; sodium hydroxide and potassium hydroxide can be commercially available. In the present invention, the concentration of the alkali solution is preferably 0.1 mol / L to 1 mol / L, more preferably 0.1 mol / L.

[0044] The present invention has no particular limitation on the amount of the alkali solution, as long as the volatiles generated by the heating treatment can be fully dissolved in the alkali solution.

[0045] Afterwards, the present invention digests the contact material obtained in step a) in the presence of an acid to obtain a second contact material solution.

[0046] In the present invention, the acid is preferably selected from one or more of hydrochloric acid, nitric acid, and sulfuric acid, preferably hydrochloric acid with a mass fraction of 36% to 38%, sulfuric acid with a mass fraction of 95% to 98%, or nitric acid with a mass fraction of 65% to 68%, and more preferably a mixed acid of hydrochloric acid and nitric acid; in a preferred embodiment of the present invention, the volume ratio of hydrochloric acid to nitric acid is 3:1. The present invention has no special restrictions on the source of the acid, and commercially available products known to those skilled in the art can be used.

[0047] In the present invention, the dosage ratio of the acid to the contact material is preferably (50-100) mL / g, that is, the dosage of the acid is preferably 5 mL-10 mL per 0.1 g of contact material, more preferably 8 mL, to ensure that the contact material can be fully dissolved.

[0048] In the present invention, in order to enable the contact material and the acid to fully react, the digestion heating rate is preferably 2°C / min to 8°C / min, more preferably 5°C / min, the temperature is preferably 100°C to 220°C, more preferably 200°C, and the insulation time is preferably 30min to 360min, more preferably 40min to 80min; on this basis, the contact material powder sample is completely digested into a clear and transparent liquid to obtain a second contact material solution.

[0049] Finally, the present invention tests the contents of lithium, aluminum and phosphorus in the second contact material solution by inductively coupled plasma atomic emission spectrometry (ICP-OES), and tests the contents of fluorine in the first contact material solution and the second contact material solution by ion chromatography (IC), thereby completing the detection of the element content of the LiAlPO4F electrolyte material.

[0050] In the present invention, the inductively coupled plasma atomic emission spectrometry is preferably performed using an inductively coupled plasma emission spectrometer well known to those skilled in the art; and the ion chromatography is preferably performed using an ion chromatograph well known to those skilled in the art.

[0051] In the present invention, the process of the inductively coupled plasma atomic emission spectrometry test is preferably specifically as follows:

[0052] (1) Pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside;

[0053] (2) The second contact material solution is diluted to 50 g with 3% nitric acid solution, 1 mL is weighed into a centrifuge tube, diluted to 50 mL with ultrapure water, shaken well, and set aside;

[0054] (3) Start the inductively coupled plasma emission spectrometer, set the test conditions, and after the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0055] In the present invention, the specific method of the volume determination in step (2) of the inductively coupled plasma atomic emission spectrometry test is not particularly limited. Preferably, the second contact material solution is constant-volume in a 50.0 mL centrifuge tube using water.

[0056] In the present invention, the test conditions in step (3) of the inductively coupled plasma atomic emission spectrometry test are preferably:

[0057] The RF power is 1kW to 1.5kW, the stabilization time is 10s to 20s, and the observation mode is radial;

[0058] More preferably:

[0059] The RF power was 1.2 kW, the stabilization time was 15 s, and the observation mode was radial.

[0060] In the present invention, the process of the ion chromatography test is preferably specifically as follows:

[0061] (1) Accurately pipette 1 mL of the F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake it well; using this solution as the mother solution, prepare a standard curve with a concentration gradient of 0.01 ppm, 0.02 ppm, 0.05 ppm, 0.1 ppm, 0.2 ppm, 0.5 ppm, and 1 ppm, shake it well, and set aside;

[0062] (2) Accurately weigh 1 g of the sample into a centrifuge tube, dilute to 50 g with ultrapure water, shake well, and set aside;

[0063] (3) Start the ion chromatograph, set the test conditions, and after the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. The standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated according to the content;

[0064] The fluorine content in the sample to be tested is obtained by subtracting the fluorine content in the blank alkali solution as in step a) from the fluorine content in the first contact material solution and the second contact material solution measured by the above ion chromatography.

[0065] In the present invention, the test conditions in step (3) of the above ion chromatography test are preferably:

[0066] Eluent A: 5mmol / L~10mmol / L sodium carbonate aqueous solution;

[0067] Eluent B: 15mmol / L~25mmol / L sodium carbonate 30%~50% acetonitrile aqueous solution;

[0068] Eluent flow rate: 0.5mL / min~1mL / min;

[0069] Injection volume: 10μL~30μL;

[0070] Column oven temperature: 30℃~50℃;

[0071] More preferably:

[0072] Eluent A: 8mmol / L sodium carbonate aqueous solution;

[0073] Eluent B: 20mmol / L sodium carbonate 40% acetonitrile aqueous solution;

[0074] Eluent flow rate: 0.75 mL / min;

[0075] Injection volume: 20 μL;

[0076] Column oven temperature: 40°C.

[0077] The present invention utilizes the property that the LiAlPO4F solid electrolyte can release the F element by pyrolysis at high temperature, directly heats the sample, and then collects the F element for IC testing; further, the aluminum phosphate, titanium phosphate and other substances generated after the pyrolysis of LiAlPO4F are completely dissolved by simple nitric acid treatment, thereby avoiding the coexistence of aluminum and fluorine elements, and the ICP test can be directly performed to obtain accurate results.

[0078] The invention provides a method for detecting the element content of a solid electrolyte material, comprising the following steps: a) heating a LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; passing the tail gas of the protective gas into an alkali solution to obtain a first contact material solution; b) digesting the contact material obtained in the step a) in the presence of an acid to obtain a second contact material solution; c) testing the contents of lithium, aluminum and phosphorus in the second contact material solution by inductively coupled plasma atomic emission spectrometry, and testing the contents of fluorine in the first contact material solution and the second contact material solution by ion chromatography, thereby completing the detection of the element content of the LiAlPO4F electrolyte material. Compared with the prior art, the detection method provided by the present invention utilizes the property of LiAlPO4F material to decompose and release F at high temperature, reduces the F content in the material by heating treatment, and avoids the coexistence of high aluminum and high fluorine to generate aluminum fluoride substances that are not easily soluble in water when directly digested with an acid solution; the decomposition products obtained after high-temperature pyrolysis treatment only need simple digestion treatment to obtain a completely digested sample; ICP-OES and IC are then used to test the element content, and accurate results can be obtained through mathematical calculations; the above technical scheme achieves overall good interaction, can accurately and effectively quantitatively determine the content of each element in the LiAlPO4F electrolyte material, is simple to operate, and the detection method is more scientific.

[0079] In order to further illustrate the present invention, the following examples are used to describe the present invention in detail. The instruments and raw materials used in the following examples of the present invention are as follows:

[0080] instrument:

[0081] Inductively coupled plasma optical emission spectrometer, ICP-OES 5800, was purchased from Agilent;

[0082] Ultrapure water machine, UPTA-10L, Shanghai Lichen Instrument Technology Co., Ltd.;

[0083] Microwave digestion instrument, M6, purchased from Shanghai Yiyao Instrument Technology Development Co., Ltd.;

[0084] Tube furnace, GSL-1700X-S, was purchased from Hefei Kejing Material Technology Co., Ltd.

[0085] raw material:

[0086] Li, Al, P, and F single element standard solutions, with a concentration of 1000 μg / mL, were purchased from the National Nonferrous Metals and Electronic Materials Analysis and Testing Center;

[0087] Sodium hydroxide, high purity, Sinopharm Chemical Reagent Co., Ltd.;

[0088] HCl, high-grade pure, was purchased from Nanjing Chemical Reagent Co., Ltd.;

[0089] Nitric acid, high-grade pure, was purchased from Nanjing Chemical Reagent Co., Ltd.;

[0090] The water used in the experiment was ultrapure water with a resistivity of 18.2 MΩ·cm;

[0091] The sample to be tested is LiAlPO4F material.

[0092] Example 1

[0093] (1) Prepare a 0.5 mol / L solution of sodium hydroxide and ultrapure water, and then divide it into two equal parts, labeled A and B, with A serving as the blank solution.

[0094] (2) Prepare 1 g of the sample to be tested and place it in a tube furnace. Dry air is continuously introduced into one end of the tube at a rate of 10 to 15 mL / min, while the other end of the tube is introduced into a 0.1 mol / L NaOH solution (Solution B).

[0095] (3) heating the mixture to 700° C. at a rate of 5° C. / min, maintaining the temperature at 700° C. for 1 h, and naturally cooling the mixture (to room temperature) to obtain a first contact material, thereby obtaining a sodium hydroxide solution to be tested (solution B).

[0096] (4) At 200° C., 0.1 g of the first contact material was placed in a microwave digestion tank (polytetrafluoroethylene digestion tank), 2 mL of nitric acid (concentration 65% to 68%) and 6 mL of hydrochloric acid (concentration 36% to 38%) were added, and the temperature was raised to 200° C. at 5° C. / min and kept warm for 60 min.

[0097] (5) After natural cooling (to room temperature), the clear solution was transferred to a centrifuge tube, and the microwave digestion tank was repeatedly rinsed with 3% nitric acid solution, and finally the volume was adjusted to 50 g to obtain the test solution C.

[0098] (6) Solutions A, B, and C were tested for fluorine content by using a Metron ion chromatograph (model 930):

[0099] a. Accurately transfer 1 mL of F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake well. Use this solution as the mother solution to prepare a standard curve with a concentration gradient of 0.01ppm, 0.02ppm, 0.05ppm, 0.1ppm, 0.2ppm, 0.5ppm, and 1ppm, shake well, and set aside.

[0100] b. Accurately weigh 1g (accurate to 1mg) of sample into a centrifuge tube, dilute to 50g with ultrapure water, shake well, and set aside.

[0101] c. Start the ion chromatograph, operate according to the operating procedures, and set the following test parameters:

[0102] Eluent A: 8mmol / L sodium carbonate aqueous solution;

[0103] Eluent B: 20mmol / L sodium carbonate 40% acetonitrile aqueous solution;

[0104] Eluent flow rate: 0.75 mL / min;

[0105] Injection volume: 20 μL;

[0106] Column oven temperature: 40°C.

[0107] After the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. A standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated based on the content.

[0108] (7) The fluorine content in solution A minus the fluorine content in solution B and C measured by IC is the F content in the sample to be tested.

[0109] (8) Sample C was tested for lithium, aluminum and phosphorus contents by ICP-OES (Agilent 5800):

[0110] a. Accurately pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside.

[0111] b. Accurately weigh 1 mL of sample solution C into a centrifuge tube, dilute to 50 mL with ultrapure water, shake well, and set aside.

[0112] c. Start the inductively coupled plasma emission spectrometer, operate according to the operating procedures, and set the following test parameters:

[0113] The test conditions of the inductively coupled plasma optical emission spectrometer were set as follows:

[0114] Working Parameters Numeric RF power / kW 1.2 Stabilization time / s 15 Observation Mode Radial

[0115] After the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0116] Example 2

[0117] (1) Prepare a 0.5 mol / L solution of sodium hydroxide and ultrapure water, and then divide it into two equal parts, labeled A and B, with A serving as the blank solution.

[0118] (2) Prepare 1 g of the sample to be tested and place it in a tube furnace. Dry air is continuously introduced into one end of the tube at a rate of 10 to 15 mL / min, while the other end of the tube is introduced into a 0.1 mol / L NaOH solution (Solution B).

[0119] (3) heating the mixture to 800° C. at a rate of 5° C. / min, maintaining the temperature at 800° C. for 1 h, and naturally cooling the mixture (to room temperature) to obtain a first contact material, thereby obtaining a sodium hydroxide solution to be tested (solution B).

[0120] (4) At 200° C., 0.1 g of the first contact material was placed in a microwave digestion tank, 2 mL of nitric acid (concentration 65% to 68%) and 6 mL of hydrochloric acid (concentration 36% to 38%) were added, and the temperature was raised to 200° C. at 5° C. / min and kept warm for 60 min.

[0121] (5) After natural cooling (to room temperature), the clear solution was transferred to a centrifuge tube, and the microwave digestion tank was repeatedly rinsed with 3% nitric acid solution, and finally the volume was adjusted to 50 g to obtain the test solution C.

[0122] (6) Solutions A, B, and C were tested for fluorine content by using a Metron ion chromatograph (model 930):

[0123] a. Accurately transfer 1 mL of F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake well. Use this solution as the mother solution to prepare a standard curve with a concentration gradient of 0.01ppm, 0.02ppm, 0.05ppm, 0.1ppm, 0.2ppm, 0.5ppm, and 1ppm, shake well, and set aside.

[0124] b. Accurately weigh 1g (accurate to 1mg) of sample into a centrifuge tube, dilute to 50g with ultrapure water, shake well, and set aside.

[0125] c. Start the ion chromatograph, operate according to the operating procedures, and set the following test parameters:

[0126] Eluent A: 8mmol / L sodium carbonate aqueous solution;

[0127] Eluent B: 20mmol / L sodium carbonate 40% acetonitrile aqueous solution;

[0128] Eluent flow rate: 0.75 mL / min;

[0129] Injection volume: 20 μL;

[0130] Column oven temperature: 40°C.

[0131] After the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. A standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated based on the content.

[0132] (7) The fluorine content of solution B and C measured by IC minus the fluorine content of solution A is the F content in the sample to be tested:

[0133] (8) Sample C was tested for lithium, aluminum and phosphorus contents by ICP-OES (Agilent 5800):

[0134] a. Accurately pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside.

[0135] b. Accurately weigh 1 mL of sample solution C into a centrifuge tube, dilute to 50 mL with ultrapure water, shake well, and set aside.

[0136] c. Start the inductively coupled plasma emission spectrometer, operate according to the operating procedures, and set the following test parameters:

[0137] The test conditions of the inductively coupled plasma optical emission spectrometer were set as follows:

[0138] Working Parameters Numeric RF power / kW 1.2 Stabilization time / s 15 Observation Mode Radial

[0139] After the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0140] Comparative Example 1

[0141] (1) Prepare a 0.5 mol / L solution of sodium hydroxide and ultrapure water, and then divide it into two equal parts, labeled A and B, with A serving as the blank solution.

[0142] (2) Prepare 1 g of the sample to be tested and place it in a tube furnace. Dry air is continuously introduced into one end of the tube at a rate of 10 to 15 mL / min, while the other end of the tube is introduced into a 0.1 mol / L NaOH solution (Solution B).

[0143] (3) heating the mixture to 600° C. at a rate of 5° C. / min, maintaining the temperature at 600° C. for 1 h, and naturally cooling the mixture (to room temperature) to obtain a first contact material, thereby obtaining a sodium hydroxide solution to be tested (solution B).

[0144] (4) At 200° C., 0.1 g of the first contact material was placed in a microwave digestion tank, 2 mL of nitric acid (concentration 65% to 68%) and 6 mL of hydrochloric acid (concentration 36% to 38%) were added, and the temperature was raised to 200° C. at 5° C. / min and kept warm for 60 min.

[0145] (5) After natural cooling (to room temperature), the clear solution was transferred to a centrifuge tube, and the microwave digestion tank was repeatedly rinsed with 3% nitric acid solution, and finally the volume was adjusted to 50 g to obtain the test solution C.

[0146] (6) Solutions A, B, and C were tested for fluorine content by using a Metron ion chromatograph (model 930):

[0147] a. Accurately transfer 1 mL of F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake well. Use this solution as the mother solution to prepare a standard curve with a concentration gradient of 0.01ppm, 0.02ppm, 0.05ppm, 0.1ppm, 0.2ppm, 0.5ppm, and 1ppm, shake well, and set aside.

[0148] b. Accurately weigh 1g (accurate to 1mg) of sample into a centrifuge tube, dilute to 50g with ultrapure water, shake well, and set aside.

[0149] c. Start the ion chromatograph, operate according to the operating procedures, and set the following test parameters:

[0150] Eluent A: 8mmol / L sodium carbonate aqueous solution;

[0151] Eluent B: 20mmol / L sodium carbonate 40% acetonitrile aqueous solution;

[0152] Eluent flow rate: 0.75 mL / min;

[0153] Injection volume: 20 μL;

[0154] Column oven temperature: 40°C.

[0155] After the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. The standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated based on the content.

[0156] (7) The fluorine content in solution A minus the fluorine content in solution B and C measured by IC is the F content in the sample to be tested.

[0157] (8) Sample C was tested for lithium, aluminum and phosphorus contents by ICP-OES (Agilent 5800):

[0158] a. Accurately pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside.

[0159] b. Accurately weigh 1 mL of sample solution C into a centrifuge tube, dilute to 50 mL with ultrapure water, shake well, and set aside.

[0160] c. Start the inductively coupled plasma emission spectrometer, operate according to the operating procedures, and set the following test parameters:

[0161] The test conditions of the inductively coupled plasma optical emission spectrometer were set as follows:

[0162] Working Parameters Numeric RF power / kW 1.2 Stabilization time / s 15 Observation Mode Radial

[0163] After the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0164] Comparative Example 2

[0165] (1) Take 0.1 g of the LAPF sample to be tested and put it into a microwave digestion tank. Add 2 mL of nitric acid (concentration 65% to 68%) and 6 mL of hydrochloric acid (concentration 36% to 38%). Heat it to 200°C at 5°C / min and keep it warm for 60 min.

[0166] (2) After natural cooling (to room temperature), the slightly turbid solution was transferred to a centrifuge tube, and the microwave digestion tank was repeatedly rinsed with 3% nitric acid solution, and finally the volume was adjusted to 50 g to obtain the test solution A.

[0167] (3) Centrifuge the test solution A at 10,000 RPM for 10 min, and take the supernatant as solution B.

[0168] (4) Solution B was tested for fluorine content by using a Metron ion chromatograph (model 930):

[0169] a. Accurately transfer 1 mL of F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake well. Use this solution as the mother solution to prepare a standard curve with a concentration gradient of 0.01ppm, 0.02ppm, 0.05ppm, 0.1ppm, 0.2ppm, 0.5ppm, and 1ppm, shake well, and set aside.

[0170] b. Accurately weigh 1g (accurate to 1mg) of sample into a centrifuge tube, dilute to 50g with ultrapure water, shake well, and set aside.

[0171] c. Start the ion chromatograph, operate according to the operating procedures, and set the following test parameters:

[0172] Eluent A: 8mmol / L sodium carbonate aqueous solution;

[0173] Eluent B: 20mmol / L sodium carbonate 40% acetonitrile aqueous solution;

[0174] Eluent flow rate: 0.75 mL / min;

[0175] Injection volume: 20 μL;

[0176] Column oven temperature: 40°C.

[0177] After the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. The standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated based on the content.

[0178] (5) Sample B was tested for lithium, aluminum and phosphorus contents by ICP-OES (Agilent 5800):

[0179] a. Accurately pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside.

[0180] b. Accurately weigh 1 mL of sample solution B into a centrifuge tube, dilute to 50 mL with ultrapure water, shake well, and set aside.

[0181] c. Start the inductively coupled plasma emission spectrometer, operate according to the operating procedures, and set the following test parameters:

[0182] The test conditions of the inductively coupled plasma optical emission spectrometer were set as follows:

[0183] Working Parameters Numeric RF power / kW 1.2 Stabilization time / s 15 Observation Mode Radial

[0184] After the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

[0185] The test results are shown in the following table:

[0186]

[0187]

[0188] In the present invention, the theoretical content refers to a solid electrolyte with a certain molecular formula, such as Li a Al b P d O e F c The theoretical content of lithium, aluminum, phosphorus and fluorine in the steel is calculated by the following formula:

[0189] Li theoretical content = M Li ×a / (M Li ×a+M Al ×b+M F ×c+M P ×d+M O ×e)×100%;

[0190] Al theoretical content = M Al ×b / (M Li ×a+M Al ×b+M F ×c+M P ×d+M O ×e)×100%;

[0191] P theoretical content = M P ×d / (M Li ×a+M Al ×b+M F ×c+M P ×d+M O ×e)×100%;

[0192] F theoretical content = M F ×c / (M Li ×a+M Al ×b+M F ×c+M P ×d+M O ×e)×100%;

[0193] Among them, M Li 、M Al 、M P 、M F 、M O They are the molar masses of lithium, aluminum, fluorine, phosphorus and oxygen respectively. When the molecular formula contains other doping elements, the calculation of the theoretical content is similar to the above and will not be repeated here.

[0194] It can be seen from the above results that by adopting the detection method provided by the present invention, the solid electrolyte is heated and digested in steps, and a solid electrolyte test solution that can be used for ICP and IC testing can be obtained, and then the content of elements such as lithium, aluminum, fluorine, and phosphorus in the solid electrolyte can be tested, and the method is simple and reliable with good reproducibility; further, by comparing Examples 1 to 2 with Comparative Examples 1 to 2, it can be seen that when the solid electrolyte solution obtained by heating pretreatment and mixed acid treatment formed by hydrochloric acid and nitric acid having a specific ratio and concentration is used for testing, the test results are more accurate and the large-scale production of aluminum fluoride substances is avoided.

[0195] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for detecting the element content of a solid electrolyte material, comprising the following steps: a) heating the LiAlPO4F electrolyte material to be tested in the presence of a protective gas to obtain a contact material; passing the protective gas tail gas into an alkali solution to obtain a first contact material solution; b) digesting the contact material obtained in step a) in the presence of an acid to obtain a second contact material solution; c) The contents of lithium, aluminum and phosphorus in the second contact material solution are tested by inductively coupled plasma atomic emission spectrometry, and the contents of fluorine in the first contact material solution and the second contact material solution are tested by ion chromatography to complete the detection of the element content of the LiAlPO4F electrolyte material.

2. The detection method according to claim 1, characterized in that: The protective gas in step a) is continuously introduced at a speed of 5 mL / min to 20 mL / min.

3. The detection method according to claim 1, characterized in that: The heating rate of the heating treatment in step a) is 2°C / min to 8°C / min, the temperature is 700°C to 1000°C, and the insulation time is 0.5h to 2h.

4. The detection method according to claim 1, characterized in that: The alkali solution in step a) is a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution; the concentration of the alkali solution is 0.1 mol / L to 1 mol / L.

5. The detection method according to claim 1, characterized in that: The acid in step b) is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid; The dosage ratio of the acid to the contact material is (50-100) mL / g.

6. The detection method according to claim 1, characterized in that: The digestion in step b) is carried out at a heating rate of 2°C / min to 8°C / min, at a temperature of 100°C to 220°C, and at a holding time of 30min to 360min.

7. The detection method according to claim 1, characterized in that: The process of the inductively coupled plasma atomic emission spectrometry test in step c) is specifically as follows: (1) Pipette 1 mg / mL standard solution of Li, Al, and P elements into a centrifuge tube, dilute to 50 mL with ultrapure water, and shake well; use this solution as the mother solution to prepare standard solutions with concentration gradients of 1 ppm, 5 ppm, 10 ppm, and 50 ppm, shake well, and set aside; (2) The second contact material solution is diluted to 50 g with 3% nitric acid solution, 1 mL is weighed into a centrifuge tube, diluted to 50 mL with ultrapure water, shaken well, and set aside; (3) Start the inductively coupled plasma emission spectrometer, set the test conditions, and after the spectrometer is stable, inject the standard curve and the sample to be tested, establish the standard curve according to the gradient concentration, and calculate the percentage of the substance to be tested in the sample according to the element response intensity in the sample to be tested.

8. The detection method according to claim 7, characterized in that: The test conditions in step (3) are: The RF power is 1 kW to 1.5 kW, the stabilization time is 10 s to 20 s, and the observation mode is radial.

9. The detection method according to claim 1, characterized in that: The process of the ion chromatography test in step c) is specifically as follows: (1) Accurately pipette 1 mL of the F element standard solution for ion chromatography analysis into a centrifuge tube, dilute it to 50 mL with ultrapure water, and shake it well; using this solution as the mother solution, prepare a standard curve with a concentration gradient of 0.01 ppm, 0.02 ppm, 0.05 ppm, 0.1 ppm, 0.2 ppm, 0.5 ppm, and 1 ppm, shake it well, and set aside; (2) Accurately weigh 1 g of the sample into a centrifuge tube, dilute to 50 g with ultrapure water, shake well, and set aside; (3) Start the ion chromatograph, set the test conditions, and after the chromatograph is stable, inject the standard curve and the sample to be tested. The workstation automatically records the chromatographic peaks and gives the retention time of the component to be tested. The standard curve is established based on the gradient concentration and peak area. Based on the retention time, peak area and content of the component to be tested, the percentage of the substance to be tested in the sample is calculated according to the content; The fluorine content in the sample to be tested is obtained by subtracting the fluorine content in the blank alkali solution as in step a) from the fluorine content in the first contact material solution and the second contact material solution measured by the above ion chromatography.

10. The detection method according to claim 9, characterized in that: The test conditions in step (3) are: Eluent A: 5mmol / L~10mmol / L sodium carbonate aqueous solution; Eluent B: 15mmol / L~25mmol / L sodium carbonate 30%~50% acetonitrile aqueous solution; Eluent flow rate: 0.5mL / min~1mL / min; Injection volume: 10μL~30μL; Column oven temperature: 30℃~50℃.

Citation Information

Patent Citations

  • Method for determining the inorganic element content in samples of lithium lanthanum zirconium oxide solid electrolyte

    CN109540874B

  • A method for processing solid electrolytes and a method for testing the elemental content in solid electrolytes.

    CN110931847B

Cited By

  • Device and method for detecting metal ions in solution based on ice water liquid-solid phase change

    CN120385670A